Vokal Tradisi Batak Toba “Andung” - Stevanie Lumbangaol; Uus Karwati; Diah Latifah (Gondang: Jurnal Seni dan Budaya, 2019)
In the current era of globalization, learning is often associated with local wisdom. The local cultural base is indeed very important, because national character is formed from cultural roots. Therefore many have raised local culture and wisdom as a basis for learning. Likewise, in the Music Education Study Program, one course is presented, namely Vocal Tradition of the Archipelago, in which there is material in the Toba Batak Tradition Vocal, Andung. Through this course, "Andung" is taught, so that the traditional vowels return and the young generation is able to appreciate them. Based on this background it is necessary to do research on the existence of Andung in the present, with the aim of reintroducing Andung as a vocal of the Toba Batak tradition. This article is a small part of the research on the development of vocal learning media for the "Andung" Toba Batak tradition. Data collection about Andung, carried out by documentation techniques, surveys and interviews. Interviewees consisted of three people, two pangandung people, one cultural observer. The data obtained are andung mabalu, andung matean ina, andung tilahaon.